Effect of shoot removal on shoot and tuberous root yields and yield components of sweet potatoes - Dahniya, M.T.; Hahn, S.K.; Oputa, C.O. (1985)
Experiments on harvesting sweet potato as a green vegetable and as a root crop are described. Whole shoots yielded 62% more than shoot tips. Similar total shoot yields were harvested whether tip removal was at two, three or four week intervals. Root yield was decreased by 31 to 48% by removing shoot tips, while removing whole shoots led to root yield decreases of 48 to 62%. Harvesting shoots at two week intervals gave 72% reduction in root yield, compared with 50% with four week intervals. There were fewer and smaller tubers as the frequency of shoot harvests increased. There were varietal differences in response to shoot removal For reasonable yields of both shoot tips and tuberous roots harvesting shoot tips at four week intervals is recommended.